PESAN SOSIAL DAN BENTUK PESAN PADA KOMIK “HAI,MIIKO!” (STUDI ANALISIS ISI) - Cicy Amelia; Evawani Elysa Lubis (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2017)
circulating in Indonesia is dominated by Japanese comics (manga) and translated and repackaged in Indonesia. The power of comics is in words and pictures. The comic